Working Towards Empirically-Based Continuous Improvements in Service Learning - Flannery, Brenda L. (Journal of business ethics, 2008)
This empirical study reports the implementation and assessment of service learning in management education. Principles of Management students worked in teams to support Campus Kitchens, a national program affiliated with colleges and universities, in recovering surplus food and delivering it to community members. Student perceptions regarding civic engagement and social responsibility, application of skills, and professional development were assessed. Two complete cycles of implementation and assessment are chronicled. The sample size for Cycle 1 was 123 students and for Cycle 2 the sample size was 91 students. The authors describe how empirical as well as anecdotal data drove the changes made to improve the service-learning experience.